PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. UNIVERSAL SUPPORT SERVICES BANDUNG - Trisna Aji, Bayu; Cay, Sam (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of training and work discipline on the performance of PT employees. Universal Support Services either partially or simultaneously. The method used is a quantitative method. The sampling technique used was saturated sampling with a sample of 75 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that training has a significant effect on employee performance with the regression equation Y = 6.155 + 0.892 Work Discipline has a significant effect on employee performance with the regression equation Y = 12.483 + 0.742 X2. Hypothesis testing obtained a calculated t value > t table or (9,148 > 1.993). Training and Work Discipline have a significant effect on employee performance with the regression equation Y = 4,780 + 0.799X1 + 0.131 This means that there is a significant simultaneous influence between training and work discipline on employee performance.